Cryopreservation of testicular tissue or testicular cell suspensions: a pivotal step in fertility preservation - Onofre, J. (Hum Reprod Update, 2016)
BACKGROUND: Germ cell depletion caused by chemical or physical toxicity, disease or genetic predisposition can occur at any age. Although semen cryopreservation is the first reflex for preserving male fertility, this cannot help out prepubertal boys. Yet, these boys do have spermatogonial stem cells (SSCs) that able to produce sperm at the start of puberty, which allows them to safeguard their fertility through testicular tissue (TT) cryopreservation. SSC transplantation (SSCT), TT grafting and recent advances in in vitro spermatogenesis have opened new possibilities to restore fertility in humans. However, these techniques are still at a research stage and their efficiency depends on the amount of SSCs available for fertility restoration. Therefore, maintaining the number of SSCs is a critical step in human fertility preservation. Standardizing a successful cryopreservation method for TT and testicular cell suspensions (TCSs) is most important before any clinical application of fertility restoration could be successful. OBJECTIVE AND RATIONALE: This review gives an overview of existing cryopreservation protocols used in different animal models and humans. Cell recovery, cell viability, tissue integrity and functional assays are taken into account. Additionally, biosafety and current perspectives in male fertility preservation are discussed. SEARCH METHODS: An extensive PubMED and MEDline database search was conducted. Relevant studies linked to the topic were identified by the search terms: cryopreservation, male fertility preservation, (immature)testicular tissue, testicular cell suspension, spermatogonial stem cell, gonadotoxicity, radiotherapy and chemotherapy. OUTCOMES: The feasibility of fertility restoration techniques using frozen-thawed TT and TCS has been proven in animal models. Efficient protocols for cryopreserving human TT exist and are currently applied in the clinic. For TCSs, the highest post-thaw viability reported after vitrification is 55.6 ± 23.8%. Yet, functional proof of fertility restoration in the human is lacking. In addition, few to no data are available on the safety aspects inherent to offspring generation with gametes derived from frozen-thawed TT or TCSs. Moreover, clarification is needed on whether it is better to cryopreserve TT or TCS. WIDER IMPLICATIONS: Fertility restoration techniques are very promising and expected to be implemented in the clinic in the near future. However, inter-center variability needs to be overcome and the gametes produced for reproduction purposes need to be subjected to safety studies. With the perspective of a future clinical application, there is a dire need to optimize and standardize cryopreservation and safety testing before using frozen-thawed TT of TCSs for fertility restoration.